59.1: A Backlight System with a Phosphor Sheet Providing both Wider Color Gamut and Higher Efficiency. Issue 1 (1st July 2013) - Ito, Yasushi; Hori, Tomomitsu; Tani, Hirofumi; Ueno, Yoshifumi; Kusunoki, Tsuneo; Nomura, Hiroshi; Kondo, Hirofumi
Abstract: A phosphor sheet in which green‐emitting thiogallate phosphor and red‐emitting sulfide phosphor are contained was developed. The LCD using it and blue LEDs can realize wider color gamut. Employing blue LEDs with spherical encapsulates in it increases light extraction of them and can provide the backlight with higher efficiency as well as wider color gamut.